Assessing the long-term effects of Basic Medical Insurance on catastrophic health spending in China. Issue 6 (3rd March 2022) - Liu, Kai; Liu, Wenting; Frank, Richard; Lu, Chunling
Abstract: Many developing countries have implemented social health insurance programmes to protect their citizens against the financial risks of seeking healthcare. While many studies have explored how individual insurance enrolments affect catastrophic health spending (CHS) in the short term, there is a lack of evidence on the long-term macro-level effects of social health insurance on CHS in low- and middle-income countries. This study examines the long-term effects of Basic Medical Insurance (BMI) on individual CHS in China, a middle-income country that has witnessed one of the highest worldwide increases in CHS rates despite its remarkable achievement of universal health insurance coverage. Specifically, we used existing longitudinal data from 1989 to 2015, therein assessing BMI policy effects by constructing two macro-level indicators, including the year of BMI presence at the prefectural level and number of years relative to BMI introduction. We employed a three-level difference-in-differences approach for the estimation. There were two main findings. First, BMI policy did not significantly reduce the probability of incurring CHS for BMI enrollees over time. Years after BMI was introduced, the policy even predicted a significant increase in the probability of incurring CHS for individuals who shifted their enrolments from traditional insurance to BMI. Second, BMI policy had spillover effects on the increase in the probability of incurring CHS for non-BMI individuals a few years after its inception. We believe there are three possible explanations for these findings: (1) shrinking BMI service coverage compared to pre-existing government-funded insurance schemes, (2) a profit-driven hospital reform that induces the overuse of expensive medicines and diagnostic tests and (3) the absence of strategic purchasing among local BMI agencies. We also discuss how relevant policy interventions may alleviate insurance-driven financial risks.